The Stylistic Device of Repetition in D H Lawrence's Short Story "The Rocking Horse Winner" - Naeem Khudair, Raghda (International Journal of Psychosocial Rehabilitation, 2020)
The present paper is about analyzing and discussing the stylistic device of repetition in D. H. Lawrence's ''The Rocking Horse Winner''. This story is selected for analysis because it includes repetition of words, phrases, and sentences. Lawrence uses repetition in the story in an effective way to show the stylistic purposes achieved by this stylistic technique, such as emphasis. Throughout the analysis and discussion of repetition in ''The Rocking Horse Winner'', it seems clear that Lawrence employs repetition (words, phrases, sentences) to achieve certain stylistic purposes that are necessary to give importance to the basic ideas in the story, such as the need for money. In ''The Rocking Horse Winner'', repetition is employed by Lawrence. A word, a phrase, or a sentence is sometimes repeated three or more times in three lines only. It has become clear that repetition is used in ''The Rocking Horse Winner'' as an effective technique. The words and clauses or sentences most commonly repeated are: there must be more money, luck, love, and know. The present paper states that the basic purpose of using repetition in Lawrence's story is 'emphasis'. The repetition makes the idea effective and draws the reader's attention to it.